(untitled) (Global Journal of Human-Social Science, 2016)
When there is no surface water we must think in use groundwater, but groundwater need treatment, Treatment of underground water one of the most difficult treatment methods, that because under groundwater contain high amount of total dissolved salts(TDS), and there is great difficulty in control the source of underground water, iron and manganese from the famous divalent elements in groundwater, the Egyptian standard for the concentration of iron is (0.3 ppm) and for manganese is (0.4 ppm) the increase in concentration for iron and manganese case change in the taste of water and sometimes effect on the human health. We will show in this study physical, chemical study for treatment of iron and manganese in groundwater.